2015
DOI: 10.1152/jn.00945.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic dendritic compartmentalization underlies stimulus-specific adaptation in an insect neuron

Abstract: Prešern J, Triblehorn JD, Schul J. Dynamic dendritic compartmentalization underlies stimulus-specific adaptation in an insect neuron. J Neurophysiol 113: 3787-3797, 2015. First published April 15, 2015 doi:10.1152/jn.00945.2014.-In many neural systems, repeated stimulation leads to stimulus-specific adaptation (SSA), with responses to repeated signals being reduced while responses to novel stimuli remain unaffected. The underlying mechanisms of SSA remain mostly hypothetical. One hypothesis is that dendritic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…The structure and response properties of prothoracic auditory interneurons are well studied (Atkins & Pollack, ; Kostarakos & Römer, ; Rheinlaender, ; Stumpner & Molina, ; Triblehorn & Schul, ), but little is known about the prothoracic auditory network and its functional design (Molina & Stumpner, ; Pollack & Imaizumi, ; Römer et al, ; Triblehorn & Schul, ). Experimental evidence indicates that local prothoracic neurons contribute to the processing of sound direction, carrier frequency, and temporal patterns in crickets (Faulkes & Pollack, ; Hardt & Watson, ; Selverston et al, ) and bush‐crickets (Prešern et al, ; Rheinlaender, ; Römer, ; Römer et al, ; Schul, ; Stumpner, ; Stumpner & Molina, ). However, besides the prominent omega neuron (ON1, Popov et al, ; Zhantiev & Korsunovskaya, ), only few local sound activated neurons in Ensifera have been studied (Stiedl et al, ; Stritih & Stumpner, ; Zhantiev & Korsunovskaya, ).…”
Section: Introductionmentioning
confidence: 99%
“…The structure and response properties of prothoracic auditory interneurons are well studied (Atkins & Pollack, ; Kostarakos & Römer, ; Rheinlaender, ; Stumpner & Molina, ; Triblehorn & Schul, ), but little is known about the prothoracic auditory network and its functional design (Molina & Stumpner, ; Pollack & Imaizumi, ; Römer et al, ; Triblehorn & Schul, ). Experimental evidence indicates that local prothoracic neurons contribute to the processing of sound direction, carrier frequency, and temporal patterns in crickets (Faulkes & Pollack, ; Hardt & Watson, ; Selverston et al, ) and bush‐crickets (Prešern et al, ; Rheinlaender, ; Römer, ; Römer et al, ; Schul, ; Stumpner, ; Stumpner & Molina, ). However, besides the prominent omega neuron (ON1, Popov et al, ; Zhantiev & Korsunovskaya, ), only few local sound activated neurons in Ensifera have been studied (Stiedl et al, ; Stritih & Stumpner, ; Zhantiev & Korsunovskaya, ).…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, the pulse rates of these species are sufficiently low as to escape the 40 -60 ms NA time constants described in the auditory pathway of crickets [43]. Interestingly, in the katydid Neoconocephalus triops, Prešern et al [44] have recently shown strong NA at the neuronal level to fast (140 p s 21 ) sound pulses but a lack of NA to slow (7 p s 21 ) sound pulses. It is also possible that the slow pulse rate does not play an important role, and these species simply show reduced or absent NA for other unknown reasons.…”
Section: Discussionmentioning
confidence: 99%
“…When the frequency spectra do differ, the strength of synaptic input from afferents may be much stronger for ultrasound than for sonic conspecifi c signals . Furthermore, local processing within a neuron's extended dendrites may allow segregation of signals differing in spectral content and temporal pattern Prešern et al 2015 ), implementing a form of auditory scene analysis or stream segregation analogous to mechanisms described for vertebrates (Moss and Surlykke 2010 ).…”
Section: Interneuronsmentioning
confidence: 99%